Avaliação da Política Nacional de Qualificação no Turismo e sua aplicação para competitividade do destino Ceará - Pinheiro, Isaac Coimbra (2024)
The National Tourism Qualification Policy (PNQT) is a strategic initiative that seeks to strengthen the competitiveness of Brazilian tourist destinations through professional qualification, aligned with the demands and dynamics of the sector. This study evaluates, in depth, the implementation of the PNQT in the state of Ceará, focusing on the period between 2021 and 2024, investigating how this policy has contributed to positioning Ceará as a competitive tourist destination. The research seeks to answer the central question: to what extent has the PNQT been effectively implemented in Ceará and what challenges and gaps compromise its ability to promote the state's tourism competitiveness? The methodological approach adopted is qualitative, of an applied nature, with exploratory and descriptive objectives. It is based on the In-Depth Assessment model, proposed by Rodrigues (2008), and uses the Thematic Analysis of Braun and Clarke (2006) to identify significant patterns in the data collected. Data collection involved documentary research, bibliographic analysis, and semi-structured interviews with public administrators, businesspeople, and community leaders. The results point to gaps in the adaptation of policy strategies to local specificities, in addition to highlighting weaknesses in interinstitutional coordination and in the integration between professional training and the real demands of the sector. However, relevant opportunities were identified to improve the implementation of the policy. When assessing the role of qualification in the competitiveness of the destination, the research concludes that, although the PNQT has generated specific improvements in the supply of tourism services, its strategic potential has not yet been fully explored. Based on these findings, the study presents practical recommendations to strengthen the effectiveness of the PNQT and maximize its contribution to the competitiveness of tourism in Ceará.